“[O]ur American kinsman”: British Nationalism and Book Reviews of American Literature in the 1840s - Lee, Sohui (Romanticism on the Net)

(untitled) (Université de Montréal, 2005)
AbstractBritish book reviews of the 1840s, particularly those analyzing the merit of American literature, provide us with an opportunity to examine how the transatlantic literary scene contributes to nation building. In examining periodical literature as a critical messenger in the circuit of transatlantic intellectual exchange, I argue that the rhetoric of Tory and Whig British reviewers of American literature were profoundly self-reflexive, demonstrating that nationalism requires the construction of dual imagined communities: within the nation and without. This literary practice, when seen as nationalist writing, suggests an invested interest not only in the shaping of an American imaginary for their audiences but also in the inevitable creation of conservative or liberal national identities for Britain.